Cytochrome c nitrite reductase: from structural to physicochemical analysis. (1st February 2005) - Burlat, B.; Gwyer, J.D.; Poock, S.; Clarke, T.; Cole, J.A.; Hemmings, A.M.; Cheesman, M.R.; Butt, J.N.; Richardson, D.J.
Abstract : The recent structural characterization of the NrfA from Escherichia coli provides a framework to rationalize the spectroscopic and functional properties of this enzyme. Analyses by EPR and magnetic CD spectroscopies have been complemented by protein-film voltammetry and these are discussed in relation to the essential structural features of the enzyme.